Visco-hyperelastic material modeling using nested linkage mechanisms. (1st June 2020) - Umut Ozcan, M; Yilmaz, Cetin; Sonmez, Fazil O.
Highlights: A mechanism-based model is developed to simulate visco-hyperelastic material response. Material nonlinearity is simulated by geometric nonlinearity of the linkage mechanism. The mechanism also displays relaxation, hysteresis and dynamic stiffness responses. The mechanical behavior of the proposed mechanism model matches test results well. Abstract: In this study, basic linear lumped elements such as springs and dashpots are used in nested linkage mechanisms in order to simulate the mechanical behavior of visco-hyperelastic materials. The proposed mechanism model containing two nested linkages can show initial softening followed by hardening response under quasi-static loading, which is commonly displayed by hyperelastic materials. Hence, material nonlinearity is simulated by geometric nonlinearity of the linkage mechanism. The mechanism also displays relaxation, hysteresis, and dynamic stiffness responses of viscoelastic materials with the help of dashpot elements. Visco-hyperelastic material behavior is closely approximated by the proposed mechanism model for the four different test scenarios, i.e., quasi-static loading, ramp-and-hold loading, hysteresis, and dynamic stiffness tests. It is shown that nonlinearity and frequency dependency of visco-hyperelastic materials is successfully captured.